GAMBARAN PERILAKU BUANG AIR BESAR SEMBARANGAN PADA MASYARAKAT DESA JATIMULYO, KABUPATEN BOJONEGORO - Rena Ratri Anggoro (Poltekkes Kemenkes Surabaya, 2017)
Jatimulyo village is one of the villages in Bojonegoro that has not been declared as ODF village. The purpose of this study was to describe the behavior of open defecation at Jatimulyo Village community. The type of this study was descriptive. The population was the total number of households (KK) in the Jatimulyo Village, sampling was conducted using cluster sampling with a sample size of 230 households. The results showed that the ownership of latrines in the community amounted to 75.65%, the people who already have latrine and used it was 100%, the people who don`t have latrines and no defecation in the latrine was 57.14%, and the people who did defecation in the river was 80.96%.Keywords : practice, open defecation, community